Relações entre consciência fonológica, escrita e leitura em testes do programa Brasil Alfabetizado - Ana Paula Campos Cavalcanti (2009)
This research attempts to comprehend how the progresses in reading and writing acquisition and the development of phonologic reflection abilities relate in learners in a process of literacy of the Youth and Adult Education (EJA Program). For the realization of this research, 70 students of the Youth and Adult Literacy (AJA Program) linked to three teaching institutions of Minas Gerais, were tested with one of the tests that the Literate Brazil Program utilizes to evaluate those who are becoming literate. The objective was to verify to what extent phonologic reflection abilities are correlated to reading and writing acquisition. To better the comprehension of the Alphabet System Appropriation process, the Psychogenesis of Writing theory, proposed by the researcher Emilia Ferreiro (FERREIRO, 1985), was used. Reading as a cognitive process of construction of the senses (CAFIERO, 2005), and the importance of the concept of letramento (SOARES, 2004)were considered in the process of literacy. Furthermore, the concept of the phonological conscience, generically defined as the capacity to consciously manipulate (move, combine or suppress) the sonorous elements of oral words (TUMER AND KOHL, 1991), was sustained. In the application of the tests, audio visual records were taken to better observe the strategies utilized by the learners at the moment of question resolution, as well as in the interviews with participants of the research. For the analysis of the data, questions of the text related to reading, writing and phonological abilities, were elected attempting to verify the possible correlation of the results. The research data evidences that even in different phases of the literacy process, exposed to different teaching methodologies or from different institutions, literacy students present little variation in the index of correct responses to questions of phonological conscience, reading and writing; suggesting a reciprocal causality of these learning processes. It is concluded that these results corroborate with research that affirms that the relation between phonological conscience and reading and writing acquisition, is of reciprocal causality, in other words, these relate amongst each other in an interactive manner (MORAIS E LIMA, 1989; MORAIS, 2004; PERFETTI et al, 1987; WAGNER, TORGENSEN E RASHOTTE, 1994).